PENGARUH PENAMBAHAN SERBUK BATA MERAH TERHADAP STABILITAS TANAH LEMPUNG SEBAGAI TANAH DASAR JALAN - Sholeh, Moch.; Novianto, Dandung; Aponno, Gerard (Media Teknik Sipil, 2012)
Dosen Teknik Sipil Politeknik Negeri MalangÂ Clay consists of grains - grains are very small (<0002 mm) and shows the nature - the natureof plasticity and cohesion. Cohesion indicates the fact that part - the part that is attached to eachother, while the plasticity is a trait that allows the form of the material was changed - edit withoutchanging the content or without returning to its original form, and without any cracks or brokens.And clay with high plasticity index has strong support low when used as a basic foundation of thehighway, so the need for soil improvement.From the above problems then this study aims to engineer clay with red brick powder in fourcomparisons. The first native land. Both the original soil mixed with red brick powder 5%. Thethird native soil mixed with red brick powder 7.5%. The four original soil mixed with red brickpowder 10%. Each of these sought specific gravity, liquid limit, plastic limit and plasticity index onthe original soil, mixing 5%, 7.5% and 10%. From the analysis of data obtained the followingconclusion: the original soil, the value amounting to 60.9 Liquid limit, plastic limit values of 42.8and plasticity index value of 18.1. The most optimal additional percentage is 7.5%. And PlasticityIndex value at 7.5% is 20,31.Key words : Red brick powder, Soil Stability, Subgrade and the Road.